Sample Preparation and Analysis for Imaging Mass Spectrometry - Edwards, Genea (Methods Mol Biol, 2017)
Imaging mass spectrometry (IMS) is a novel quantitative technique used to investigative diverse biomolecules on tissue sections. Specifically, IMS uses analytical power of mass spectrometry to determine the spatial distribution of certain metabolites and/or proteins located directly on biological sections from a single tissue sample. Typically, IMS is combined with histological analysis to reveal additional distribution details of characterized biomolecules including cell type and/or subcellular localization. In this chapter we describe the use of Matrix-Assisted Laser Desorption/Ionization (MALDI) Time-Of-Flight/Time-Of-Flight (TOF/TOF) to analyze various cholesterol and phosphatidylcholine species in atherosclerotic plaque of murine heart aortic valves. In particular we detail animals used, tissue collection, preparation, matrix application, spectra acquisition for generating a color coded image based on IMS spectral characteristics.